Developing Sustainable Behaviors for Underground Heritage Tourism Management: The Case of Persian Qanats, a UNESCO World Heritage Property - Hossein Mousazadeh; Amir Ghorbani; Hossein Azadi; Farahnaz Akbarzadeh Almani; Ali Zangiabadi; Kai Zhu; Lóránt Dénes Dávid (Land, 2023)
The Persian Qanats, ancient underground aqueduct systems that have provided irrigation water to arid regions in Iran for over 3000 years, are recognized as a vital element of the country’s cultural heritage. Eleven of these impressive structures have been included on the UNESCO World Heritage List, underlining their cultural, social, political, and physical significance. As these underground heritage sites offer a unique opportunity for fostering territorial collaboration and social capital between tourists and the local community, it is important to develop a comprehensive model to influence the behavior of tourists, officials, and natives in their treatment of these invaluable sites. This study aimed to design a sustainable behavior model for underground heritage tourism management in Persian Qanats that have been listed as UNESCO World Heritage properties. The research employed a theme analysis approach, utilizing a statistical sample of 22 base managers and Qanat tourism experts. The study used content and thematic analysis to develop a research model that guarantees the sustainable protection of these valuable underground heritage sites by shaping the behavior of tourists, officials, and natives. The proposed model serves as a guideline for effective behavior management, leading to the preservation of these significant underground heritage sites for future generations. In conclusion, this study provides valuable insights into the sustainable management of Persian Qanats and the promotion of a strong sense of territorial collaboration and social capital between tourists and the local community.